Amoebic Liver Abscess Multifocal With Bilateral Parapneumonic Effusion: A Case Report - Bayu Arief Hartanto; Arnelis; Fauzar; Wahyudi (Talenta Publisher, 2024)
Background: A liver abscess is defined as a pus-filled mass in the liver that can develop from injury to the liver or an intraabdominal infection disseminated from the portal circulation. Objective: The aim was to discuss about liver abscesses are categorized into pyogenic or amoebic caused by Entamoeba histolytica. Methods: This is a case report that reported about pus-filled mass in the liver. Results: A male patient, 53 years old, was admitted to Hospital for Upper right abdominal pain, Fever, Cough, Pain in the lower right chest. Chest examination found weakened bronchovesicular breath sounds as high as RIC V, Pleural Friction Rub, wet crackles. Abdominal Examination found supel palpation, liver palpable 2 fingers below the arcus costae and 2 fingers below the process xiphoid, blunt edge, soft consistency, tenderness pain in the dextra hypochondrium. Laboratory report Anti Amoeba : Positive 40,3 unit. The patient was given intravenous metronidazole therapy 3x750 mg for 10 days. Conclusion: Complications of amoebic liver abscess is pleuropulmonary involvement. Pulmonary and pleural amebiasis is an uncommon disease, usually occurring on the right side of the lung compared to the left side.